The transcription factor calcium‐response factor limits NMDA receptor‐dependent transcription in the developing brain. Issue 2 (15th February 2016) - Lyons, Michelle R.; Chen, Liang‐Fu; Deng, Jie V.; Finn, Caitlin; Pfenning, Andreas R.; Sabhlok, Aditi; Wilson, Kelli M.; West, Anne E.
Abstract: Neuronal activity sculpts brain development by inducing the transcription of genes such as brain‐derived neurotrophic factor ( Bdnf ) that modulate the function of synapses. Sensory experience is transduced into changes in gene transcription via the activation of calcium signaling pathways downstream of both L‐type voltage‐gated calcium channels (L‐VGCCs) and NMDA‐type glutamate receptors (NMDARs). These signaling pathways converge on the regulation of transcription factors including calcium‐response factor (CaRF). Although CaRF is dispensable for the transcriptional induction of Bdnf following the activation of L‐VGCCs, here we show that the loss of CaRF leads to enhanced NMDAR‐dependent transcription of Bdnf as well as Arc . We identify the NMDAR subunit‐encoding gene Grin3a as a regulatory target of CaRF, and we show that expression of both Carf and Grin3a is depressed by the elevation of intracellular calcium, linking the function of this transcriptional regulatory pathway to neuronal activity. We find that light‐dependent activation of Bdnf and Arc transcription is enhanced in the visual cortex of young CaRF knockout mice, suggesting a role for CaRF‐dependent dampening of NMDAR‐dependent transcription in the developing brain. Finally, we demonstrate that enhanced Bdnf expression in CaRF‐lacking neurons increases inhibitory synapse formation. Taken together, these data reveal a novel role for CaRF as an upstream regulator of NMDAR‐dependent gene transcription and synapse formation in the developing brain. NMDARs promote brain development by inducing the transcription of genes, including brain‐derived neurotrophic factor (BDNF). We show that the transcription factor calcium‐response factor (CaRF) limits NMDAR‐dependent BDNF induction by regulating expression of the NMDAR subunit GluN3A. Loss of CaRF leads to enhanced BDNF‐dependent GABAergic synapse formation indicating the importance of this process for brain development. Our observation that both CaRF and GluN3A are down‐regulated by intracellular calcium suggests that this may be a mechanism for experience‐dependent modulation of synapse formation. Abstract : NMDARs promote brain development by inducing the transcription of genes, including brain‐derived neurotrophic factor (BDNF). We show that the transcription factor calcium‐response factor (CaRF) limits NMDAR‐dependent BDNF induction by regulating expression of the NMDAR subunit GluN3A. Loss of CaRF leads to enhanced BDNF‐dependent GABAergic synapse formation indicating the importance of this process for brain development. Our observation that both CaRF and GluN3A are down‐regulated by intracellular calcium suggests that this may be a mechanism for experience‐dependent modulation of synapse formation.